Securing the commons in India: Mapping polycentric governance - Meinzen-Dick, Ruth S.; Rao, Jagdeesh Puppala; Chaturvedi, Rahul; Rao, Kaushalendra; Bruns, Bryan Randolph; Kandikuppa, Sandeep; ElDidi, Hagar (International Food Policy Research Institute, 2020)
Common pool land and water resources in India play vital, but often overlooked, roles in livelihoods and ecosystem services. These resources are subject to the authority of various government departments and are often managed in ways that result in uncertain tenure for the people who depend on these resources for fodder, fuel, water, and other products. An Indian NGO, the Foundation for Ecological Security (FES), has developed a process for “commoning”—assisting communities to secure the commons by forming inclusive local institutions to manage the resources, and to work with different government departments to gain stronger rights to the commons. This paper applies polycentricity theory to examine the institutional arrangements that govern the commons in FES sites in Andhra Pradesh and Karnataka states and assesses relationships that may affect commons management. It draws on key informant interviews and village-level social network mapping exercises (Net-mapping) to show the complex flows of resources, information, and influence related to the commons among habitation-level organizations, local government, resource agencies, the rural employment guarantee program (MGNREGA), and NGOs. This paper discusses the potential of this methodology as a diagnostic tool to help understand community perceptions of the role of various stakeholders in overall governance of the commons, and can provide guidance for interventions to help communities to strengthen their tenure on the commons and management of those resources.